PTH pulsatility but not calcium sensitivity is restored after total parathyroidectomy with heterotopic autotransplantation - Schmitt, Claus P.; Wenning, Swee; Mehls, Otto; Veldhuis, Johannes D.; Lehnert, Thomas; Ritz, Eberhard; Schaefer, Franz (Journal of the American Society of Nephrology, 2003)
In healthy humans, parathyroid hormone (PTH) is secreted via basal mode with superimposed oscillatory bursts every 8 to 12 min. Amplitude and frequency changes mediate the instantaneous response of the parathyroids to changes in ambient Ca2+ concentrations. The parathyroid gland tetrad may be synchronized by autonomic innervation. This study investigated the effect of total parathyroidectomy and heterotopic autotransplantation of parathyroid tissue (PTX) on PTH secretion patterns in nine patients with end-stage renal disease.
Gesehen am 15.01.2021